Mapping of vertical geochemical zonation by the example of gold field Chertovo Koryto (the Patom upland) - Roman Gavrilov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
In order to determine the location of mineralization levels on the surface the geochemical data processing has been carried out on the secondary dispersion halos of mesothermal gold field Chertovo Koryto. Rock samples from surface mine openings and core of verticalexploration wells were in the base of investigation. The obtained analytical data were processed by means of the discriminant analysis based on "recognition of images". It was established that geochemical ranges of above-, middle- and below ore levels of a gold field have essential distinctions. As a result of division of the massif of geochemical samples on the basis of their classification as reference samples, three levels of mineralization were determined on the deposit area. The paper introduces the principal possibility of applying discriminant analysis for mapping gold mineralization levels.